REPRESENTATION OF HUMAN NATURE IN ANIMATED CHARACTERS: A SEMIOTIC STUDY OF SHAUN THE SHEEP SERIES - Wildani, Nurul; Lestari, Nurul; Hasbi, Muh. (Journal of English Literature and Linguistic Studies, 2024)
AbstractThe purpose of this research is to analyze the denotative, connotative, and mythical meaning of the characters in Shaun the Sheep series and to reveal the representation of human nature in the animated characters of Shaun the Sheep series. This research uses a qualitative descriptive approach and uses Roland Barthes semiotic analysis. The focus of this research is visual and gesture analysis. The results of this study include (1) Showing the existence of denotative, connotative and mythical forms of meaning. (2) Representing human nature in "Shaun the Sheep" series, starting from Shaun the main character who is described as the leader of the flock because he has a smart brain and high self-confidence, Bitzer the sheepdog who is very loyal to his master, Shirley is the biggest sheep among the other sheep because he always eats more food than the others, Slip the homeless dog, a pair of twin lambs (The twins), The Pigs and Pidsley.